Perceptions of politics and organizational justice on bank employees - Nurmalasari, Fitri; Suhariadi, Fendy; Subhekti, Erick Fajar (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
This study aims to investigate the organizational politics perception of bank employees and its impact on organizational justice perception and performance. A comparative descriptive qualitative analysis method was used to analyze data obtained from literature review and field research. Purposive sampling technique was employed to determine 5 informants, with key informants being managers in a bank in Surabaya. The results showed that organizational politics in the bank is relatively high and has a negative impact on employees' organizational justice perception. The contribution of this research lies in providing a deeper understanding of organizational politics in the banking industry and offering guidance for management to enhance efficiency and the quality of the work environment.